International political economy contrasting world views - Miller, Raymond C. (Routledge, 2008)
Written in a concise and accessible style, this text equips students with the necessary skills and knowledge to understand this complex area. Engaging with both classical theories and the main contemporary debates, this provides a starting point for the study of IPE.